The characteristics of the sentinel lymph node metastasis in predicting the axillary lymph node status in patients with breast carcinoma - Olszewski, Wojciech P.; Szumera-Ciećkiewicz, Anna; Piechocki, Jacek; Towpik, Edward; Olszewski, Włodzimierz T. (Polish Journal of Pathology, 2009)
Introduction: Lymph node metastases are the most significant prognostic factors in patients with breast carcinoma. A positive sentinel lymph node (SLN) biopsy is followed by an axillary lymph node (ALN) dissection. In sentinel lymph node negative cases the risk of positive non-sentinel ALN is very low though not absent. The aim of this study was to determine predictive factors for non-sentinel lymph node metastases on the basis of sentinel lymph node metastasis characteristics as well as features of the primary tumour. Material and methods: 128 patients who had a positive SLN biopsy for breast carcinoma in 2005-2007 were identified. The breast carcinoma metastases in each SLN were assessed according to their location within the node (subcapsular, mixed subcapsular and parenchymal, parenchymal, multifocal or extensive) and metastatic infiltration of perinodal tissue was also reported. These data were correlated with the ALN involvement and characteristics of the primary tumour. Results: The strong predictors of the ALN metastasis included the SLN metastasis diameter (7.6 vs. 4.4 mm) and size classified according to WHO classi- fication (ITC 0 vs. 100%, micrometastasis 23.5 vs. 76.5%, macrometastasis 51.9 vs. 48.1%). The SLN metastases with a diameter of above 3 mm were associated with approximately twice more frequent ALN metastases. In an extensive location of SLN metastasis the highest percentage of ALN metastases was found (65 vs. 35%). The weak predictors of ALN metastases were: primary tumor diameter (> 2 cm), immunohistochemical HER2 positive status, infiltration of sentinel perinodal tissue by metastasis, histological primary tumour grade. Conclusions: Some additional details, which can be easily evaluated in a routine SLN examination in breast carcinoma, have a predictive value of the ALN metastatic status and should be included in the histopathological report.